Exploring the anti-gastric cancer mechanisms of Diosgenin through integrated network analysis, bioinformatics, single-cell sequencing, and cell experiments - Yun, Zhangjun; Yang, Qianru; Xue, Chengyuan; Shen, Yang; Lv, Liyuan; Mi, Suicai; Hou, Li (Frontiers in Pharmacology, 2025)
BackgroundTo comprehensively investigate the mechanism of action of Diosgenin elements against gastric cancer (GC).MethodsTargets of Diosgenin were collected from six databases, and enrichment analysis was used to identify its associated diseases and biological pathways. GC-related genes were identified using weighted gene co-expression network analysis. A multi-approach strategy, including network analysis, bioinformatics, single-cell RNA sequencing, Mendelian randomization, and cell experiments, was used to explore the anti-GC mechanisms of Diosgenin.ResultsIn this study, 605 Diosgenin targets were identified, with key involvement in cell apoptosis, TNF signaling, and platinum resistance pathways, demonstrating significant enrichment in GC. Diosgenin may exert its anti-GC effects through 311 targets, involving regulation of the cell cycle, p53, and FoxO signaling pathway. Key effectors, including CDK1, CCNA2, TOP2A, CHEK1, and PLK1, were identified. Single-cell sequencing indicated that TOP2A, HSP90AA1, and HSP90AB1 might be crucial immune regulatory targets of Diosgenin. Diosgenin significantly inhibited GC cell proliferation, colony formation, migration, and invasion. Evidence from western blot analysis indicates that Diosgenin exerts anti-GC effects by suppressing the expression of PLK1 and MDM2 proteins while upregulating p53 protein levels.ConclusionThese findings highlight Diosgenin’s potential as a promising therapeutic agent for GC, offering a foundation for future research and clinical applications.